Addiction to work and factors relating to this: a cross-sectional study on doctors in the state of Paraíba - Azevedo, Walter Fernandes; Mathias, Lígia Andrade da Silva Telles (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Addiction to work is one of the new behavioral phenomena present in organizations and it is characterized by excess work and compulsion to work. This phenomenon may give rise to different sicknesses and may affect different professionals, including doctors. Thus, the aims of this study were to analyze the factorial validity and internal consistency of the Dutch Work Addiction Scale (DUWAS); to evaluate the prevalence of addiction to work among doctors in the state of Paraíba; and to investigate factors relating to addiction to work among these doctors. DESIGN AND SETTING: This was an exploratory, descriptive cross-sectional study with a quantitative approach conducted in municipalities in the state of Paraíba.METHODS: Data were gathered between June and October 2015, by applying a questionnaire containing sociodemographic questions and the Work Addiction Scale. RESULTS: The results showed that the Work Addiction Scale has internal consistency and factorial validity and that, in the population studied, only one factor was pointed out: addiction to work. Most of the doctors were not addicted to work; among the addicts, the addiction was not excessive; and the addiction had a positive correlation with the number of shifts done and a negative correlation with age. CONCLUSION: Greater attention to this phenomenon is required and further research on this topic is needed in order to elucidate the harm caused by addiction to work in daily medical practice.